2020
DOI: 10.3390/cancers12061545
|View full text |Cite
|
Sign up to set email alerts
|

RAC1B Induces SMAD7 via USP26 to Suppress TGFβ1-Dependent Cell Migration in Mesenchymal-Subtype Carcinoma Cells

Abstract: The small GTPase RAC1B has been shown to act as a powerful inhibitor of the transforming growth factor (TGF)β type I receptor ALK5 and TGFβ1/ALK5-induced epithelial–mesenchymal transition and cell motility. However, the precise mechanism has remained elusive. RNAi-mediated knockdown of RAC1B in the pancreatic ductal adenocarcinoma (PDAC)-derived cell line Panc1 failed to alter transcriptional activity from a transfected ALK5 promoter–reporter construct. In contrast, pharmacological inhibition of the proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Recently, we demonstrated in pancreatic epithelial cells that RAC1B promoted the expression of CDH1 (encoding E-cadherin, ECAD) and other epithelial genes, while inhibiting the expression of mesenchymal genes and EMT [15,16]. Mechanistically, RAC1B-dependent protection from mesenchymal conversion and acquisition of a motile phenotype was due to suppression of tumorpromoting MEK-ERK2 signaling [15,16] and interference with TGFβ1 signaling via downregulation of the TGFβ type I receptor ALK5 [4] and induction of the inhibitory Smad, SMAD7 [17]. We also observed that RAC1B upregulated SMAD3 which in its non-activated form exhibited an anti-migratory effect in pancreatic cancer cells [18] presumably due to its ability to promote the expression of ECAD, via transcriptional induction of miR-200 [19], or biglycan (BGN), a pericellular proteoglycan and potent TGFβ inhibitor [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated in pancreatic epithelial cells that RAC1B promoted the expression of CDH1 (encoding E-cadherin, ECAD) and other epithelial genes, while inhibiting the expression of mesenchymal genes and EMT [15,16]. Mechanistically, RAC1B-dependent protection from mesenchymal conversion and acquisition of a motile phenotype was due to suppression of tumorpromoting MEK-ERK2 signaling [15,16] and interference with TGFβ1 signaling via downregulation of the TGFβ type I receptor ALK5 [4] and induction of the inhibitory Smad, SMAD7 [17]. We also observed that RAC1B upregulated SMAD3 which in its non-activated form exhibited an anti-migratory effect in pancreatic cancer cells [18] presumably due to its ability to promote the expression of ECAD, via transcriptional induction of miR-200 [19], or biglycan (BGN), a pericellular proteoglycan and potent TGFβ inhibitor [18].…”
Section: Introductionmentioning
confidence: 99%
“…Activated ALK5 is known to recruit SMAD7 in a complex with the E3 ligase Smurf2 to promote its internalization and eventual proteasomal degradation in order to terminate TGFβ signaling. Earlier, we demonstrated that the suppressive effect of RAC1B on ALK5 was dependent on SMAD7, and further that RAC1B upregulated protein expression of SMAD7 via intermittent induction of USP26 (see Section 4.2.1 ) [ 84 ].…”
Section: Interaction Of Rac1 With Tgfβ Signalingmentioning
confidence: 99%
“…SMAD7 . In a recent study, we have shown that i) RAC1B promotes the expression of SMAD7 and ii) SMAD7 mediates the suppressive effect of RAC1B on ALK5 protein and its associated kinase activity [ 84 ]. We further revealed that upregulation of SMAD7 by RAC1B requires the rapid transcriptional induction of USP26 [ 84 ].…”
Section: Interaction Of Rac1 With Tgfβ Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles by Dr. Hendrick Ungefroren’s group contribute to the role of the constitutively active Rac1B splice variant in transforming growth factor (TGFβ) signaling [ 8 , 9 ]. The authors elucidate the mechanisms by which Rac1B acts to inhibit TGFβ-1-dependent cell migration.…”
mentioning
confidence: 99%